Ocean acidification and the Permo-Triassic mass extinction - Clarkson, M. O.; Kasemann, S. A.; Wood, R. A.; Lenton, T. M.; Daines, S. J.; Richoz, S.; Ohnemueller, F.; Meixner, A.; Poulton, S. W.; Tipper, E. T. (Science, 2015)
Ocean acidification triggered by Siberian Trap volcanism was a possible kill mechanism for the Permo-Triassic Boundary mass extinction, but direct evidence for an acidification event is lacking. We present a high-resolution seawater pH record across this interval, using boron isotope data combined with a quantitative modeling approach. In the latest Permian, increased ocean alkalinity primed the Earth system with a low level of atmospheric CO2 and a high ocean buffering capacity. The first phase of extinction was coincident with a slow injection of carbon into the atmosphere, and ocean pH remained stable. During the second extinction pulse, however, a rapid and large injection of carbon caused an abrupt acidification event that drove the preferential loss of heavily calcified marine biota. Ocean acidification and mass extinction The largest mass extinction in Earth's history occurred at the Permian-Triassic boundary 252 million years ago. Several ideas have been proposed for what devastated marine life, but scant direct evidence exists. Clarkson et al. measured boron isotopes across this period as a highly sensitive proxy for seawater pH. It appears that, although the oceans buffered the acidifiying effects of carbon release from contemporary pulses of volcanism, buffering failed when volcanism increased during the formation of the Siberian Traps. The result was a widespread drop in ocean pH and the elimination of shell-forming organisms. Science, this issue p. 229